Maternal risk factors for paediatric inguinal hernia. Issue 1 (20th October 2021) - Auger, Nathalie; del Giorgio, Francesca; Le-Nguyen, Annie; Bilodeau-Bertrand, Marianne; Piché, Nelson
Abstract: Background: Risk factors for paediatric inguinal hernia are poorly understood. This longitudinal cohort study assessed whether children with a maternal history of inguinal hernia or connective tissue disorders have a higher risk of developing inguinal hernias before 13 years of age. Methods: The study included children followed up between birth and 13 years of age in Quebec, Canada, 2006–2019. Newborns whose mothers had inguinal hernias or connective tissue disorders were followed over time to identify future hospital admissions for inguinal hernia. Cox proportional hazards regression adjusted for patient characteristics was used to estimate hazard ratios (HRs) and 95 per cent confidence intervals for the association between maternal hernia or connective tissue disorders and future childhood hernias. Associations in girls and boys were examined separately. Results: The study included 786 322 children with 6 186 448 person-years of follow-up. There were 6861 children with inguinal hernias, corresponding to an incidence of 11.1 per 10 000 person-years. Children with a maternal history of inguinal hernia had 2.92 (95 per cent c.i. 2.39 to 3.58) times the risk of having inguinal hernias relative to children whose mothers had no such history. Children with a maternal history of connective tissue disorders had 1.30 (1.00 to 1.68) times the risk. Maternal hernias were strongly associated with risk of inguinal hernias in girls (HR 5.34, 3.82 to 7.47), whereas maternal connective tissue disorders were associated with inguinal hernias in boys (HR 1.35, 1.02 to 1.79). Conclusion: Paediatric inguinal hernias may be associated with maternal inguinal hernias and connective tissue disorders, but the underlying reason for this relationship requires further investigation. Lay Summary: In this study of 786 322 children in Canada from 2006 to 2019, it was found that children whose mothers had an inguinal hernia or connective tissue disorder were more at risk of developing a hernia themselves. Repairs for inguinal hernia are among the most common operations performed in children. The results showed that girls whose mothers had an inguinal hernia had more than five times the risk of developing an inguinal hernia before 13 years of age. Boys whose mothers had connective tissue disorders had a 35 per cent greater risk of inguinal hernia. These findings suggest that inguinal hernias may be inherited. Abstract : In this cohort study of over 785 000 children, maternal inguinal hernia was associated with risk of paediatric inguinal hernias, especially in girls. Maternal connective tissue disorders were associated with risk of inguinal hernias in boys only.